Adoption of emerging ICTs: The role of actors in a social network - Hart O. Awa; Ojiabo Ukoha; Best C. Eke (Cogent Business & Management, 2016)
This paper uses actor network theory (ANT) to provide further insight into ICT adoption framework by showing how the diverse actors in small service(s) businesses guarantee continuous adoption of emerging ICT amidst many influences. On the basis of purposive sampling, unstructured and semi-structured interviews were conducted with 21 respondents from fast food organizations and IT firms. However, despite the opposition amongst the actors in the socio-technical network, ICT innovations are often adopted by small service businesses though the managers' adoption decision is regularly shaped by various factors which in turn reinforce other actors' pre-conceived beliefs, attitudes and values. Adoption follows a dynamic path based on trial and error and each stage is vital, distinct, integrated and provides different implication(s). The proposed framework supports all sizes of businesses but each stage in the adoption process is treated on its own merit.
Keywords: 650